Communication break down: Typology of telecommunications provisions in regional trade agreements - José-Antonio Monteiro; Kian Cassehgari Posada; L. Lee Tuthill (World Trade Organization (WTO), 2022)
Although a growing number of regional trade agreements (RTAs) include telecommunications provisions, the collection and systematization of information on telecommunications provisions in RTAs remain limited. This paper addresses this gap by mapping and reviewing the different types of provisions on telecommunications found in RTAs that have been notified to the World Trade Organization (WTO). The analysis reveals that telecommunications provisions in RTAs cover a broad range of regulatory issues, from access and use to anticompetition to standards and technical regulations and cooperation. While some telecommunications provisions, in particular on telecommunications services, replicate existing WTO rules, many other provisions add clarifications or expand some of the disciplines set out in the WTO agreements. At the same time, new types of provisions have been devised to address new regulatory and technological issues, including mobile services, internet access and consumer rights. These new provisions, consistent with the overall aim of the WTO rules, aim at fostering a pro-competitive regulatory framework of the telecommunications sector.
Keywords: F13; F15; 330; World Trade Organization; Regional Trade Agreements; Telecommunications; Digital economy